Pengaruh Model Bermain Peran Berbasis Budaya Lokal Terhadap Kemampuan Sosial-Emosional Anak Usia 5–6 Tahun - Ahmad Zainul Irfan; Nurul Iman; Lalu Sirajul Hadi; Baiq Sarlita Kartiani (Jurnal Eduforia: Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
This study aims to evaluate the effectiveness of a local culture-based role-play model in enhancing the social-emotional competence of early childhood learners. Employing a quasi-experimental pretest–posttest control group design, the study involved children aged 5–6 years enrolled in early childhood education (ECE) institutions. The intervention was conducted over 6–8 weeks, consisting of 2–3 sessions per week using role-play scenarios derived from local folklore and cultural values. Social-emotional competence was measured using culturally adapted versions of the Strengths and Difficulties Questionnaire (SDQ) and the Assessment, Evaluation, and Programming System (AEPS). ANCOVA results revealed significant improvements in the treatment group compared to the control group, particularly in areas of empathy, emotional regulation, and prosocial behavior. The intervention’s effectiveness was reinforced by high fidelity of implementation and active involvement of teachers and parents. These findings underscore the potential of integrating local cultural elements into learning models as a culturally responsive strategy to foster social-emotional development and curriculum relevance in ECE settings. The study recommends national-level adoption of such programs through targeted teacher training and community-based curriculum design as part of a sustainable early childhood education framework.